La implementación del derecho del demandado a reclamar costas en los procesos de alimentos y paternidad, cuando el examen de ADN es negativo. - Carrera García, Jocelin Roxana (2023)
As stated in the procedure established in the Organic Code for Children and Adolescents, when the presumed father implied by the mother is not the father of the minor according to the negative result of the DNA test, the judge must revoke the responsibility to feed, in a decision that cannot be questioned by the judge because it is supported by law; however, even if the law has provided due controls and rigor for this type of examination, there will always be the possibility of a margin of error. According to an analysis, it is necessary to establish that, since the validity of the reformatory law to the Code of Childhood and Adolescence, carried out in 2009, it was incorporated into Ecuadorian legislation, in matters of the Family Women, Children and Adolescents, the parameters under which the DNA test must be carried out, also regulating the sufficiency of its result as irrefutable proof in the alimony and paternity processes, that is, the rules regarding everything related to the scientific test are established, based on the genetic. Finally, it is important to establish that: The norm warns that, if only the defendant does not appear for the DNA test in two indications, the judge can even "presume" that he is the biological father, on the contrary, it happens with the mother, against whom there is no coercive norm. that forces him to appear for a DNA test in cases of paternity challenge, or nullity of recognition. This would also cause social problems for the defendant, such as losing his home, job, among others. Therefore, this would allow the legislator to evaluate and/or regulate these reforms, to balance the rights and obligations of both the plaintiff and the defendant. Keyword: Law of Claim, Alimony, Paternity, negative DNA.